2023
DOI: 10.1097/lvt.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Bacterascites confers poor patient prognosis beyond MELD prediction

Abstract: Spontaneous bacterial peritonitis (SBP) is a well-recognized clinical entity with a poor prognosis. In comparison, the prevalence, microbiological flora, and prognostic significance of bacterascites (BA) (the presence of organism on culture but ascitic PMN <250 cells/mm³) is largely unknown. We, therefore, assessed the prognosis and predictors of outcome in patients with BA in comparison with those with SBP. Ascitic fluid cultures from consecutive patients with cirrhosis from 2008 to 2018 were reviewed retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…King et al [ 9 ] evaluated retrospectively 176 cases of SBP and 213 cases of BA from 2008 to 2018. The authors found that the SBP patients had significantly higher Model for End-Stage Liver Disease (MELD) scores, peripheral blood white cell counts, and rates of Enterobacteriaceae and MDR.…”
Section: The Thorny Issue Of Spontaneous Ascitic Fluid Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…King et al [ 9 ] evaluated retrospectively 176 cases of SBP and 213 cases of BA from 2008 to 2018. The authors found that the SBP patients had significantly higher Model for End-Stage Liver Disease (MELD) scores, peripheral blood white cell counts, and rates of Enterobacteriaceae and MDR.…”
Section: The Thorny Issue Of Spontaneous Ascitic Fluid Infectionmentioning
confidence: 99%
“…Patients with SBP had a lower survival rate at 30 d and 3 mo compared to BA, but no significant difference remained at 6 mo and beyond. The predicted mortality calculated by the MELD score alone was significantly lower than the mortality across all MELD groups for both SBP and BA; BA had a greater negative impact on patient survival than what was predicted by the MELD score[ 9 ]. The mortality rates are certainly not unequivocal in cirrhotic patients, and mortality does not depend on infection alone but in primis on liver and kidney function and the timeliness of medical treatment.…”
Section: The Thorny Issue Of Spontaneous Ascitic Fluid Infectionmentioning
confidence: 99%
“…Es wäre interessant zu erfahren, ob zwischen beiden Gruppen ein Unterschied hinsichtlich der Inzidenz von bakteriellen Infektionen bestand, da Probiotika in einigen Studien die Rate an Infektionen senken konnten 1 . Infektionen wie die spontan bakterielle Peritonitis führen wiederum zu einer Verschlechterung der Leberfunktion und der Prognose der Patienten vor Lebertransplantation 2 . Schade ist weiterhin, dass die Autoren Patienten mit cholestatischen Erkrankungen ausgeschlossen haben, weil gerade diese Gruppe häufig Infektionen entwickelt.…”
unclassified
“…6 /L. These outcomes were chosen due to their direct association with poor prognosis and high mortality[7,11].2023 Arzivian et al Cureus 15(12): e50191. DOI 10.7759/cureus.50191…”
mentioning
confidence: 99%